The Presentation Of Imagery And Expressive Means In Artistic Translation On The Example Of Feya Mora’s Novel "You Are A Different World To Me" - Mukhtorova, Muslima (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article is devoted to the study of the characteristics of the reflection of the artistic imagery and expressive means used in Feya Mora’s novel "You Are a Different World" in translation into the Uzbek language. It analyzes the types of imagery and expressive means found in the work, their role in enriching the content of the text and enhancing the ideological and aesthetic impact. The importance of artistic means in ensuring the integrity of the text and in expressing events more vividly and effectively is also highlighted. In the process of research, the original text of the work and the Uzbek translation were comparatively analyzed, and attention was paid to the extent to which such arts as simile, animation, and closed metaphor (allusion) were preserved in the translation. The article substantiates that the priority task in translation is not only word-for-word correspondence, but also the transmission of content and artistic spirit. In conclusion, it is emphasized that the Uzbek translation adequately reflects the artistic and aesthetic value of the work.